2015
DOI: 10.1080/02786826.2015.1121198
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological characterization of particulate emissions from straw,Miscanthus, and poplar pellet combustion in residential boilers

Abstract: Wood pellets have been used in domestic heating appliances for three decades. However, because the share of renewable energy for heating will likely rise over the next several years, alternative biomass fuels, such as short-rotation coppice or energy crops, will be utilized. We tested particulate emissions from the combustion of standard softwood pellets and three alternative pellets (poplar, Miscanthus sp., and wheat straw) for their ability to induce inflammatory, cytotoxic, and genotoxic responses in a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
(31 reference statements)
5
11
3
Order By: Relevance
“…Our results are not consistent with those of Kasurinen et al (2015b), who reported that none of the particle-bound PAHs concentrations were significantly lower in the PM 1 emissions from Miscanthus sp. pellets (97 mg/kg) than in the PM 1 emissions from softwood (401 mg/kg), poplar (37 mg/kg) or wheat-straw pellets (128 mg/kg).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results are not consistent with those of Kasurinen et al (2015b), who reported that none of the particle-bound PAHs concentrations were significantly lower in the PM 1 emissions from Miscanthus sp. pellets (97 mg/kg) than in the PM 1 emissions from softwood (401 mg/kg), poplar (37 mg/kg) or wheat-straw pellets (128 mg/kg).…”
Section: Resultscontrasting
confidence: 99%
“…While the MSPM 0.4–1 contained relatively high levels of Zn (>2 g/kg), it did not induce toxicological responses in the human lung cells used in this study. This is not in agreement with the results of Kasurinen et al (2015b), who found that the Zn-rich and PAH-poor PM 1 emissions from combustion of Miscanthus (pellets) induced a strong cytotoxic response. Moreover, Kasurinen et al (2015b).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations